Ending hunger in Asia and the Pacific by 2030: An assessment of investment requirements in agriculture - International Food Policy Research Institute; Asian Development Bank; Rosegrant, Mark W.; Perez, Nicostrato D.; Valmonte-Santos, Rowena; Danessi, Lorena (Asian Development Bank, 2019)
About 518 million people in Asia and the Pacific suffered from hunger in 2017—1 million more than in the previous year. Farmers face challenges such as shrinking natural resources, degrading environments, and declining labor availability in addition to climate change and financial non-viability. The demand for food and nutrition is also increasing. With all this, more investment in agriculture is needed to accomplish Sustainable Development Goal 2—ending hunger and malnutrition by 2030. In the report, findings presented were taken from the analysis of recent trends in food security, gross domestic product, and population growth as well as agricultural supply, demand, and trade.